The Influence of the Village Community Empowerment Base on the Creativity of Village Community Groups to Increase Standard of Living in Villages in the Covid-19 Era - Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Universitas Nahdlatul Ulama Lampung, 2021)
Community empowerment is the existence of equality or equal position between the community and institutions that carry out community empowerment programs, both for men and women. The dynamics that are built are the relation of equality with the development of mechanisms from each other's knowledge, experience, and expertise. Each of them acknowledges each other's strengths and weaknesses so that there is a mutual learning process. Empowerment programs that can stimulate community independence are programs that are participatory, planned, carried out, supervised, and evaluated by the community. But getting to that level requires time and a mentoring process that includes facilitators who have a high commitment to community empowerment. The principle of self-reliance is to respect and prioritize community abilities compared to assistance from other parties. This concept does not view the poor as incapable objects (the save not), but as subjects who have little ability (the have litte). They have the ability to save in-depth knowledge about business problems, know about their environmental conditions, have the workforce and the will and have long-complied social norms. All of these must be explored and used as basic capital for the empowerment process. Assistance from other parties which is material in nature must be seen as a support, so that the provision of assistance does not weaken the level of self-reliance.